Security Informatics - Yang, Christopher C.; Chau, Michael; Wang, Jau-Hwang.; Chen, Hsinchun; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
Intelligence and Security Informatics (ISI) is defined as the study of the development and use of advanced information systems and technologies for national, international, and societal security-related applications. With the rise of global terrorism, the field has been given an increasing amount of attention from academic researchers, law enforcement, intelligent experts, information technology consultants and practitioners. SECURITY INFORMATICS is global in scope and perspective. Leading experts will be invited as contributing authors from the US, UK, Denmark, Israel, Singapore, Hong Kong, Taiwan, Europe, etc. It is the first systematic, archival volume treatment of the field and will cover the very latest advances in ISI research and practice. It is organized in four major subject areas: (1) Information and Systems Security, (2) Information Sharing and Analysis in Security Informatics, (3) Infrastructure Protection and Emergency Responses, and (4) National Security and Terrorism Informatics.
Framing Social Movement Identity with Cyber-Artifacts: A Case Study of the International Falun Gong Movement -- Patterns of Word Use for Deception in Testimony -- Information Integration for Terrorist or Criminal Social Networks -- Processing Constrained k-Closest Pairs Queries in Crime Databases -- What-If Emergency Response Through Higher Order Voronoi Diagrams -- Identity Management Architecture -- A Game Theoretic Framework for Multi-agent Deployment in Intrusion Detection Systems -- ETKnet: A Distributed Network System for Sharing Event Data and Multi-faceted Knowledge in a Collaboration Federation -- Duplicate Work Reduction in Business Continuity and Risk Management Processes.
Keywords: Computer science; Computer network architectures; Data protection; Data mining; Artificial intelligence; Management information systems; Computer Science; Systems and Data Security; Business Information Systems; Data Mining and Knowledge Discovery; Operations Research/Decision Theory; Computer Systems Organization and Communication Networks; Artificial Intelligence (incl. Robotics).